Pleiotropic Functions of the Chromodomain-Containing Protein Hat-trick During Oogenesis in Drosophila melanogaster. Issue 3 (1st March 2018) - Singh, Ankita; Dutta, Debdeep; Paul, Maimuna Sali; Verma, Dipti; Mutsuddi, Mousumi; Mukherjee, Ashim
Abstract: Chromatin-remodeling proteins have a profound role in the transcriptional regulation of gene expression during development. Here, we have shown that the chromodomain-containing protein Hat-trick is predominantly expressed within the oocyte nucleus, specifically within the heterochromatinized karyosome, and that a mild expression is observed in follicle cells. Colocalization of Hat-trick with Heterochromatin Protein 1 and synaptonemal complex component C(3)G along with the diffused karyosome after hat-trick downregulation shows the role of this protein in heterochromatin clustering and karyosome maintenance. Germline mosaic analysis reveals that hat-trick is required for maintaining the dorso-ventral patterning of eggs by regulating the expression of Gurken. The increased incidence of double-strand breaks (DSBs), delayed DSB repair, defects in karyosome formation, altered Vasa mobility, and, consequently, misexpression and altered localization of Gurken in hat-trick mutant egg chambers clearly suggest a putative involvement of Hat-trick in the early stages of oogenesis. In addition, based on phenotypic observations in hat-trick mutant egg chambers, we speculate a substantial role of hat-trick in cystoblast proliferation, oocyte determination, nurse cell endoreplication, germ cell positioning, cyst encapsulation, and nurse cell migration. Our results demonstrate that hat-trick has profound pleiotropic functions during oogenesis in Drosophila melanogaster .